Naturalismo domesticado, o pseudorrealismo na crítica de Theodor W. Adorno à indústria cultural - Abel Camilo de Oliveira Lage Filho (2010)
The aim of this work was to research the role of domesticated naturalism, the pseudo realism in the process of manipulation and control of the masses in Adornos critique of culture industry. This study begins locating the domesticated naturalism as a component of the elucidation, related to domination of human inner nature and external nature and, after that, it shows how culture industry uses this element of enlightenment to convert it into a mystification of the masses. Afterwards, it contrasts the pseudo realism of new form of ideology with the mimesis of reality in literary realism and naturalism. At the end, considering the dialectic of the particular and universal, this work demonstrates how technical reproducibility of the cultural product produces the simple reproduction of the spirit and how the autonomy of the work of art contributes, on the other hand, to the expanded reproduction of the spirit.